Neonatal Screening: Cost-utility Analysis for Galactosemia - Nahid HATAM; Mehrdad ASKARIAN; Samad SHIRVANI; Elham SIAVASHI (Tehran University of Medical Sciences, 2017)
Background: Galactosemia is a congenital metabolic disorder that can damage the health of a newborn. Screening is an important step to prevent and treat this condition. Due to increasing health care costs and limited financial resources of health systems, the most suitable economic analysis tool should be applied. The aim of this study was to analyze the cost-utility of neonatal screening program for diagnosing galactosemia in Fars province, Iran. Methods: In this cross-sectional study and cost-utility analysis in the cost of screening for galactosemia and its financial effects, decision tree model and society's viewpoint were used. The population of study was 81837 infants referred to Neonatal Screening Laboratory (Nader Kazemi Clinic) affiliated to Shiraz University of Medical Sciences (SUMS), Iran, in 2010. Quality of life in two groups of patients was evaluated by using the time trade-off. The best intervention option was selected by using the Incremental Cost-effectiveness Ratio. Results: The estimated cost of diagnosed through screening and without screening were 43519911 and 130011168 Iranian Rails (4222.00 $ and 12615.00 $), respectively. Therefore, there was a saving of 201443240.99 Iranian Rails (19641.00 $), for each patient annually. Conclusion: The screening program can improve both the qualitative and quantitative lifestyle of people and increase savings in health care system. Policymakers could use the results to design new policies based on the necessity of screening.